Crew Resource Management in the Intensive Care Unit: a prospective 3‐year cohort study. Issue 10 (16th June 2015) - Haerkens, M. H. T. M.; Kox, M.; Lemson, J.; Houterman, S.; van der Hoeven, J. G.; Pickkers, P.
<x xml:space="preserve">Abstract</x> Background Human factors account for the majority of adverse events in both aviation and medicine. Human factors awareness training entitled "Crew Resource Management (CRM)" is associated with improved aviation safety. We determined whether implementation of CRM impacts outcome in critically ill patients. Methods We performed a prospective 3‐year cohort study in a 32‐bed ICU, admitting 2500–3000 patients yearly. At the end of the baseline year, all personnel received CRM training, followed by 1 year of implementation. The third year was defined as the clinical effect year. All 7271 patients admitted to the ICU in the study period were included. The primary outcome measure was ICU complication rate. Secondary outcome measures were ICU and hospital length of stay, and standardized mortality ratio. Results Occurrence of serious complications was 67.1/1000 patients and 66.4/1000 patients during the baseline and implementation year respectively, decreasing to 50.9/1000 patients in the post‐implementation year (P = 0.03). Adjusted odds ratios for occurrence of complications were 0.92 (95% CI 0.71‐1.19, P = 0.52) and 0.66 (95% CI 0.51‐0.87, P = 0.003) in the implementation and post‐implementation year. The incidence of cardiac arrests was 9.2/1000 patients and 8.3/1000 patients during the baseline and implementation year, decreasing to 3.5/1000 patients (P = 0.04) in the post‐implementation year, while cardiopulmonary resuscitation success rate increased from 19% to 55% and 67% (P = 0.02). Standardized mortality ratio decreased from 0.72 (95% CI 0.63‐0.81) in the baseline year to 0.60 (95% CI 0.53‐0.67) in the post‐implementation year (P = 0.04). Conclusion Our data indicate an association between CRM implementation and reduction in serious complications and lower mortality in critically ill patients.